Association of tethering of the second‐order chords and prolapse of the first‐order chords of the anterior leaflet: A risk factor for early and late repair failure. Issue 4 (19th February 2020) - Calafiore, Antonio M.; Totaro, Antonio; Testa, Nicola; Sacra, Cosimo; Calvo, Eugenio; Di Mauro, Michele
Abstract: Background and Aim: Second‐order chord tethering of the anterior leaflet is a risk factor for failure of posterior leaflet prolapse repair. Materials and Methods: We describe two cases of second‐order chord tethering of the anterior leaflet associated with severe mitral regurgitation due to prolapse or chordal rupture of the anterior leaflet, causing early and late failure of repair. Results: We described two cases where this phenomenon happened. Conclusions: Our cases demonstrate that the second‐order chords of the prolapsing AL can be tethered and that this aspect should be carefully evaluated before surgery, as it can progress over time, affecting the results of surgical repair.